Analisis Variasi Faktor Eksposi Terhadap Contrast To Noise Ratio (CNR) Citra Cranium Proyeksi Antero Posterior - Wahdini Hanifah; Dewilza, Nerifa; Nisa, Chairun; Yudha, Sagita; Kirana, Keisya Salsabila (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2026)
The quality of radiographic images is highly dependent on exposure factors including tube voltage (kV), tube current and exposure time (mAs). The Contrast to Noise Ratio value can transmit image quality, a higher CNR indicates a good image with less interference (noise). The study aims to determine the effect of exposure factor variations on the CNR value and which exposure factors that produce optimal CNR in AP cranium projections. This study uses a quantitative method, an experimental study at the Radiology Installation of the Siti Rahmah Padang Islamic Hospital in September 2024. Data were obtained from cranium phantom images with variations in tube voltage (kV) 68, 74, and 78, and current and exposure time (mAs) 10, 12, and 14. The images were analyzed using the Radiant DICOM Viewer application with the ROI technique to calculate the CNR value in the anatomical area, namely the frontal, crista gali, mandible, both orbits and the background. The ROI results were analyzed using multiple linear regression tests. The results showed that the variation of exposure factors had a significant effect on the CNR value of 94.7%. The optimal exposure factor, at 68 kV and 14 mAs, with the highest CNR of 44.598. The lowest CNR value at an exposure factor of 78 kV and 10 mAs was 22.063. These results can be used as a reference in determining the optimal exposure factor in AP cranium examination